Relevansi Prinsip Siyasah Dusturriyah (Politik Ketatanegaraaan Islam) Terhadap Hierarki Peraturan Perundang-Undangan di Indonesia - Akhmad Hafi; Noormala Santi; Akhmad Zaki Yamani (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
This study aims to examine the relevance of siyasah dusturiyyah principles (Islamic constitutional politics) to the hierarchy of legislation in Indonesia. Using a qualitative approach with a normative-philosophical analysis method, this research explores fundamental values such as syura (consultation), al-‘adl (justice), maslahah (public interest), and tha‘at li al-imam (obedience to legitimate authority), as well as their contribution to the formation of national law. The findings reveal a strong alignment between the principles of siyasah dusturiyyah and the fundamental norms of lawmaking as stipulated in Law No. 12 of 2011 in conjunction with Law No. 13 of 2022. The principle of syura is reflected in participatory legislative processes, al-‘adl in the enforcement of substantive justice, and maslahah in the orientation of law toward public benefit. The integration of these Islamic values strengthens the moral legitimacy of national law, promotes governmental transparency, and deepens the dimension of social justice. This study emphasizes that the contextual application of siyasah dusturiyyah can serve as an ethical foundation for Indonesia’s legal system—one that is democratic, just, and oriented toward the welfare of the people within a pluralistic state framework.